Elevated temperatures interact with habitat quality to undermine survival of ectotherms in climatic refugia. Issue 2 (16th October 2014) - Penk, Marcin; Donohue, Ian; Récoules, Vincent; Irvine, Kenneth; Thuiller, Wilfried
Abstract Aim Large‐scale effects of climatic fluctuations can be masked by local microclimatic variability, allowing species to retain fragments of their original ranges. However, downscaling predicted ecological effects of climate change to local scales and individual species comprises a key knowledge gap. As temperature modifies both abiotic and biotic processes, the fate of refugial populations may depend on interactions of temperature with susceptibility of organisms to other factors, rather than on the impact of temperature alone. To explore this, we examined whether temperature regulates the sensitivity to hypoxia of an aquatic glacial relict, Mysis salemaai, an opossum shrimp. Location Loughs Oughter, Allen and Derg (field surveys) and Dublin (laboratory experiments), Ireland. Methods We used laboratory experiments to determine thermal sensitivity of M. salemaai and quantify the effect of temperature on survival and regulation of aerobic metabolism in progressive hypoxia. The resulting temperature and oxygen sensitivity thresholds were then validated in the field. Results Survival of M. salemaai in reduced oxygen conditions was significantly lower at higher temperatures, even though the tested temperature range did not cause mortality on its own. Results of respiration assays suggest that this was a consequence of impaired capacity at elevated temperatures for regulating oxygen uptake in hypoxic conditions. Main conclusions Our findings demonstrate that biological effects of climate warming can depend more strongly on interactions of temperature with other factors than on the effects of elevated temperatures alone. Understanding species‐specific responses to such interactions is essential to predict future distribution patterns, mitigate threats and prioritize conservation measures aimed at preserving global biodiversity.